2001
DOI: 10.1103/physrevlett.86.119
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Formation in a Thin Solid Film with Interactions

Abstract: We investigate a new type of surface instability of a thin elastic film subjected to surface interactions such as van der Waals and electrostatic forces from another solid surface in its vicinity. It is found that a sufficiently soft (shear modulus <10 MPa) and nearly incompressible film deforms to form an undulating pattern without any mass transport. A novel feature is that the characteristic length scale of the pattern is nearly independent of the nature and magnitude of the external force, but varies linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
242
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(263 citation statements)
references
References 17 publications
20
242
1
Order By: Relevance
“…Slip BC at the bottom: The solution of the elastostatic problem with the slip BC at the bottom, Eqs. (10,11), is the Airy stress function Eq. (A1) given in appendix A.…”
Section: Grinfeld Instability -Classical Way Of Calculation; Effementioning
confidence: 99%
See 1 more Smart Citation
“…Slip BC at the bottom: The solution of the elastostatic problem with the slip BC at the bottom, Eqs. (10,11), is the Airy stress function Eq. (A1) given in appendix A.…”
Section: Grinfeld Instability -Classical Way Of Calculation; Effementioning
confidence: 99%
“…In polymer films, however, this coupling should be present and important. Moreover this term establishes the connection to other elastic instabilities, namely to a buckling-like instability under compressive stress and, in the case of an externally applied field, to the elasto-electric instability investigated by Sharma et al [11][12][13][14]. Finally the growth rate of the height of the polymer film is derived in case of simultaneous action of stress and external field.…”
Section: Introductionmentioning
confidence: 99%
“…In their works on solid elastic films with a contactor, Mönch and Herminghaus (2001) and Shenoy and Sharma (2001) showed that a surface instability is manifested in the absence of residual stress. As mentioned in the Introduction, we are interested in how the addition of a superficial residual stress affects the stability of the surface with a proximate contactor.…”
Section: Linearizationmentioning
confidence: 99%
“…Considering such material to inhabit a half-space, we impose force balance both in the bulk and on the surface. The interaction of a rigid contactor with a surface is accounted for by a potential (Mönch and Herminghaus 2001; Podio-Guidugli 1988; Podio-Guidugli and Caffarelli 1990; Shenoy and Sharma 2001). From the resulting linearized bulk and superficial equations, we derive a dispersion relation and find parameter values for which stable or unstable behavior of the film surface is manifested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation